Scar satisfaction and body image in thyroidectomy patients: prospective study in a tertiary referral centre. Issue 1 (16th November 2017) - Sethukumar, P; Ly, D; Awad, Z; Tolley, N S
Abstract: Background: This study is the first to evaluate scar satisfaction and body image in thyroidectomy patients using validated assessment tools. Methods: A total of 123 thyroidectomy patients were recruited over 8 months. Both patients and clinicians completed assessment tools that included: the Manchester Scar Scale (to measure scar perception), Dysmorphic Concern Questionnaire (to assess body image), Body Dysmorphic Concern Questionnaire (to screen for body dysmorphic disorder) and EQ-5D (to measure life quality). A separate image panel comprising experts and non-experts assessed 15 scar photographs. The results were analysed using non-parametric descriptive statistics. Results: Poor body image was associated with poor scar perception (ρ = 0.178, p = 0.05). Poor life quality correlated with poor scar perception (ρ = −0.292, p = 0.001). Scar length did not affect scar perception. Prevalence of body dysmorphic disorder among patients was found to be 8.94 per cent, which is higher than general population rates. Conclusion: Negative body image and life quality impact negatively upon scar perception.